Pathological and Biochemical Assessment of Renal Function in Diabetic Patients - Fawaz Fathel Abd; Shaiban Mohammed Hussein; Afrah Jalal Abd Al Kadhim; Masar Ihsan Ali; Noor Alhuda Mohammed Radhi (American Journal of Biomedicine and Pharmacy, 2025)
Diabetes is a chronic elevated glucose level in blood which leads to a cluster of various complications involving multi-organ damage and dysfunction . Diabetic Nephropathy is the one of the major microvascular complications of Diabetes Mellitus which leads to the development of end stage renal disease (ESRD). Assessing the renal functional status in diabetic patients is challenge at initial stages of the disease. Present study aims to assess the renal functional status on patients with type I and II Diabetes Mellitus. Altogether, 100 age and sex matched individuals were included in this case control study with groups of 50 diabetic and 50 non-diabetic individuals. Multiple biochemical parameters were evaluated with hospitalization at STMH Muzaffarabad. Statistically significant values of blood glucose, Urobilinogen, Serum Creatinine and Urinary Protein were established in Diabetic individuals as compared to controls (P<0.05). All other parameters showed no significant values between both groups. In diabetic patients there were more derangements in the parameters indicative of renal dysfunctions. The better understanding of the pathophysiology helps in better management of the glycemic and non-glycemic factors in diabetic patients. Diabetes is a state of chronic hyperglycemia resulting from defects of insulin secretion and/or insulin action. The consequences of these abnormalities or their combinations are a wide variety of metabolic derangements producing damage, dysfunction, and failure of various organs, especially the kidneys, peripheral nerves, heart and blood vessels. Diabetes Mellitus (DM) is characterized by a progressive decline in insulin secretion by beta cells in response to rising glucose as in Type 1 diabetes and a progressive decline in response to incretin hormone glucagon-like peptide, GLP-1 as in Type 2 diabetes resulting in chronic hyperglycemia. Diabetic nephropathy (DN) is defined as a gradual decline in glomerular filtration rate (GFR) with rise in i.e., creatinine and excretion of specific markers of kidney damage like albuminuria. The evolution of DN was thought to take place in 4 stages. Stage 1 includes the minimal diffuse glomerulosclerosis and effacement of the foot processes. Stage 2 comprises diffuse glomerulosclerosis with zone of glomerular stella in the nonhypertensive patients.